Fuzzy Logic Hysteresis Control of А Single-Phase on-Grid Inverter: Computer Investigation - Angelina Tomova; Mihail Antchev; Mariya Petkova; Hristo Antchev (Institute of Advanced Engineering and Science, 2013)
This paper presents a realization of fuzzy-logic hysteresis control of а single-phase on-grid inverter. The inverter used for the research is implemented by the full-bridge power circuit and it is connected to the utility grid by means of LCL filter. For the purpose of the computer simulation the relative mathematical equations are issued. The research of the model established by these equations is done by means of computer simulation with the software MATLAB/SIMULINK. The operation of the model combines two non-linear control methods - fuzzy control and hysteresis control. Simulation results and their analysis are included. The operation of the model of the inverter is analyzed in two different cases of the output power of the system - 800W and 1600W approximately.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.3606